Characterization of Atmospheric Icing Conditions during the HALO-(AC)3 Campaign with the Nevzorov Probe and the Backscatter Cloud Probe with Polarization Detection - Johannes Lucke; Tina Jurkat-Witschas; Darrel Baumgardner; Frank Kalinka; Manuel Moser; Elena de la Torre Castro; Christiane Voigt (SAE Technical Paper Series, SAE Technical Paper Series, 2023)
The measurement and in-flight characterization of atmospheric icing conditions remains a challenging task. This is due to the large variability of microphysical properties of icing conditions. Icing may occur in pure supercooled liquid clouds of various droplet sizes, it may contain freezing drizzle or freezing rain drops and it also takes place in various types of mixed-phase conditions. A sensor or a combination of sensors to discriminate these icing environments would therefore be beneficial. Especially the phase classification of small cloud particles is still difficult to assess. Within the SENS4ICE project, the German Aerospace Center (DLR) suggests the use of the Nevzorov probe and the Backscatter Cloud Probe with Polarization Detection (BCPD) for the detection and differentiation of icing conditions during research missions that lack standard underwing probes. The first research flights with this instrument combination were conducted in March and April 2022 out of Longyearbyen, Svalbard in the scope of the HALO-(AC) 3 campaign. The Polar 6 aircraft of the Alfred-Wegener-Institut was equipped with the two sensors and other established microphysical cloud probes for validation. Here, we demonstrate our evaluation strategy of the two instruments and show how their data can be used to assess microphysical cloud conditions. We test this evaluation strategy on the basis of one research flight during which a large variety of icing conditions occurred. Furthermore, we also show a comparison of our results to the predictions of the icing warning system ADWICE of the German Weather Service.